98.9k views
5 votes
translate each Graph as specified below(a)the graph of y=(x)+4 is shown. Translate it to get the graph of y=f(x)+4(b) The graph of y=g(x) is shown. Translate it to get the graph of y=g(x-2).

translate each Graph as specified below(a)the graph of y=(x)+4 is shown. Translate-example-1
User Nima
by
4.9k points

1 Answer

2 votes

Solution:

Given the graphs (a) and (b)

a) The function of graph (a) is


f(x)=-4√(x+3)+1

The graph of the function is shown below

Translating it to get the graph of


y=f(x)+4

The translated function becomes


\begin{gathered} y=f(x)+4 \\ y=(-4√(x+3)+1)+4 \\ y=-4√(x+3)+1+4 \\ y=-4√(x+3)+5 \end{gathered}

The translated graph is

b) The function of graph (a) is


g(x)=-|x|

The graph of the function is shown below

Translating it to get the graph of


y=g(x-2)

The translated function becomes


\begin{gathered} y=g(x-2) \\ y=-|x-2| \end{gathered}

The translated graph is



translate each Graph as specified below(a)the graph of y=(x)+4 is shown. Translate-example-1
translate each Graph as specified below(a)the graph of y=(x)+4 is shown. Translate-example-2
translate each Graph as specified below(a)the graph of y=(x)+4 is shown. Translate-example-3
translate each Graph as specified below(a)the graph of y=(x)+4 is shown. Translate-example-4
User JamesHoux
by
4.5k points